Sistema web de gestión de trámites departamentales del Gobierno Autónomo Descentralizado Municipal del Cantón Chone - Pachard Vélez, Servio Gabriel (2020)
The proposal of the present degree work was to develop a web system for the management of departmental procedures that are carried out in Chone Decentralized Autonomous Government. The system is modified using the Extreme Programming XP methodology; in the planning phase, user stories were defined, the personnel involved were identified, roles were assigned, deliverables and delivery times were defined, in the design phase, Class-Responsibility-Collaborator cards, diagrams of classes and respective system interfaces, for the job development phase, the Model-View-Controller software architecture pattern, the PHP Laravel 5.8 Framework, the MySQL database manager system and other essential development technologies from web systems like JavaScript, HTML5, Bootstrap, Ajax; in the testing phase to verify the operation of the system, black box tests were carried out on each of the modules that comprise it. At the end of the extreme programming methodology, a web management system capable of automating the departmental procedures of the GADM in Chone will be obtained; to finish this degree work, the technology transfer was made to the Chone GADM, providing this entity with the DEPARTMENTAL PROCEDURES MANAGEMENT WEB SYSTEM.